Collaborative learning - Medina Gonzáles, Silvia Elisa (2017)
Collaborative learning is a process consisting of learning activities specifically designed for peer work or interactive groups of students with common objectives. During this process, the teacher plays the role of learning facilitator. It is important to consider learning can be enhanced through the mobilization of collective intelligence, this can be achieved through new teaching practices. Several studies have been related about the effects of collaborative learning, some researchers affirm that the most benefited are low performing students because they receive the support of higher level students who support them during the process.